2001
DOI: 10.1046/j.1365-8711.2001.04699.x
|View full text |Cite
|
Sign up to set email alerts
|

Chandra observations of the X-ray jet in 3C 66B

Abstract: A B S T R A C TOur Chandra observation of the FR I radio galaxy 3C 66B has resulted in the first detection of an X-ray counterpart to the previously known radio, infrared and optical jet. The X-ray jet is detected up to 7 arcsec from the core and has a steep X-ray spectrum, a < 1:3^0:1. The overall X-ray flux density and spectrum of the jet are consistent with a synchrotron origin for the X-ray emission. However, the inner knot in the jet has a higher ratio of X-ray to radio emission than the others. This sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
53
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(66 citation statements)
references
References 35 publications
(45 reference statements)
11
53
2
Order By: Relevance
“…Similar offsets have been observed in other kpc‐scale jets (e.g. Dulwich et al 2007; Hardcastle et al 2001, in 3C 15 and 3C 66B, respectively), although their underlying cause is currently not well understood. Even if the shock speed was included in the model and constrained using the X‐ray emission lifetime, the geometry would remain under‐determined, since there are still more free parameters than observables.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Similar offsets have been observed in other kpc‐scale jets (e.g. Dulwich et al 2007; Hardcastle et al 2001, in 3C 15 and 3C 66B, respectively), although their underlying cause is currently not well understood. Even if the shock speed was included in the model and constrained using the X‐ray emission lifetime, the geometry would remain under‐determined, since there are still more free parameters than observables.…”
Section: Discussionsupporting
confidence: 69%
“…Observations of nearby sources at shorter wavelengths often show a close correspondence to the radio morphology and characteristic spectral energy distributions, suggesting that synchrotron radiation from energetic particles also dominates the emission in the optical (e.g. Keel 1988; Fedorenko & Courvoisier 1996) and X‐ray (Worrall, Birkinshaw & Hardcastle 2001; Hardcastle, Birkinshaw & Worrall 2001). High‐energy electrons (γ= E / mc 2 ∼ 10 7 –10 8 ) radiate at optical and X‐ray wavelengths and have very short synchrotron‐emitting lifetimes (10 2 –10 3 yr in a magnetic field of a few nT), and must therefore be reaccelerated locally to maintain the observed emissions.…”
Section: Introductionmentioning
confidence: 89%
“…These exciting observations have revealed that X-ray jets extend up to hundreds of kpc and are dominated by emission from bright jet knots and terminal hotspots. In low-power FR I jets, the optical/near-IR and X-ray fluxes fit on an extrapolation of the radio spectra (e.g., [6][7][8]), consistent with a single-population synchrotron origin for the emission all the way from radio through X-ray energies. However, more powerful FR II (quasar) jets have very different spectral energy distributions (SEDs), with the observed X-rays being harder and at a higher flux than expected from extrapolating the radio-to-optical synchrotron spectrum, suggesting that they are part of a separate spectral component (Figure 1b).…”
Section: Introductionmentioning
confidence: 63%
“…Finally, jets in a number of FR I sources (including 3C 31) have been detected at X‐ray and/or optical wavelengths (e.g. Hardcastle, Birkinshaw & Worrall 2001; Hardcastle et al 2002; Worrall, Birkinshaw & Hardcastle 2001; Sparks et al 2000; Kraft et al 2002; Perlman et al 2001; Marshall et al 2002). The radiation is most plausibly produced by the synchrotron process over the entire observed frequency range, and the shape of the spectrum therefore carries information about particle acceleration and energy loss.…”
Section: Summary and Suggestions For Further Workmentioning
confidence: 99%